The major medical ethical challenges facing the public and healthcare providers in Saudi Arabia - Abdulaziz F Alkabba; Ghaiath M. A. Hussein; Adnan A Albar; Ahmad A Bahnassy; Mahdi Qadi (Wolters Kluwer Medknow Publications, 2012)
Background: Despite the relatively high expenditure on healthcare in Saudi Arabia, its health system remains highly centralized in the main cities with its primary focus on secondary and tertiary care rather than primary care. This has led to numerous ethical challenges for the healthcare providers. This article reports the results of a study conducted with a panel of practitioners, and non-clinicians, in Saudi Arabia, in order to identify the top ten ethical challenges for healthcare providers, patients, and their families. Materials and Methods: The study design was a cross-sectional, descriptive, and qualitative one. The participants were asked the question: "What top ten ethical challenges are Saudis likely to face in health care?" The participants were asked to rank the top ten ethical challenges throughout a modified Delphi process, using a ranking Scale. A consensus was reached after three rounds of questions and an experts' meeting. Results: The major 10 ethical issues, as perceived by the participants in order of their importance, were: (1) Patients' Rights, (2) Equity of resources, (3) Confidentiality of the patients, (4) Patient Safety, (5) Conflict of Interests, (6) Ethics of privatization, (7) Informed Consent, (8) Dealing with the opposite sex, (9) Beginning and end of life, and (10) Healthcare team ethics. Conclusion: Although many of the challenges listed by the participants have received significant public and specialized attention worldwide, scant attention has been paid to these top challenges in Saudi Arabia. We propose several possible steps to help address these key challenges.